2002
DOI: 10.1046/j.1365-2613.2002.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro examination of an extracellular matrix scaffold for use in wound healing

Abstract: Summary. This paper describes evidence that an extracellular matrix (ECM) secreted by human umbilical vein endothelial cells (HUVECs) assembled on gelatin coated plates overlaid by a mixed matrix secreted by human dermal microvascular endothelial cells (HDMECs) and human dermal fibroblasts provides a viable acellular scaffold for use in wound healing. Trypsinized epidermal keratinocytes or colonies from Dispase-digested fresh and cadaver skin tissue adhered and proliferated on either HUVECs ECM/gelatin or mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“…Specifically, dispase treatment removes the lamina densa (rich in type IV collagen), but preserves type VII collagen-containing anchoring fibrils. [52][53][54] However, a study using collagenase treatment showed that the fibronectin matrix of human periodontal ligament cells was maintained in a cell sheet after 2 h. 55 Finally, Lim et al reported the disruption of several ECM ultrastructures with increasing duration of dispase incubation, indicating that it may be possible to reduce the ECM even further using dispase. 56 Thus, our dispase-based partial-lift technique results in a cell sheet with minimal ECM and the advantages of being readily performed, biocompatible, and open for manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, dispase treatment removes the lamina densa (rich in type IV collagen), but preserves type VII collagen-containing anchoring fibrils. [52][53][54] However, a study using collagenase treatment showed that the fibronectin matrix of human periodontal ligament cells was maintained in a cell sheet after 2 h. 55 Finally, Lim et al reported the disruption of several ECM ultrastructures with increasing duration of dispase incubation, indicating that it may be possible to reduce the ECM even further using dispase. 56 Thus, our dispase-based partial-lift technique results in a cell sheet with minimal ECM and the advantages of being readily performed, biocompatible, and open for manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…A skin segment will be broken down into its cellular compartments with a singular enzymatic use to achieve separation of the epidermis from the dermis. This author has described full details of these methods in previous publications [4] [12].…”
Section: Conceptmentioning
confidence: 99%
“…This has not been attempted in any study thus far and will provide hopefully, an accelerated means of restoring the epithelial barrier. If a delay is sought, for example, to wait until wound exudate has ceased or cultured, it is known that the epidermal rosettes do maintain their structural integrity in vitro as was clearly observed when a co-culture of epidermal rosettes, dermal microvascular endothelial cells and dermal fibroblasts was attempted [12]. They do not shed their load of cells onto a plastic surface; only onto a cell matrix [4].…”
Section: Epidermismentioning
confidence: 99%
See 2 more Smart Citations